2017
DOI: 10.1002/stem.2721
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Parthenogenetic Embryonic Stem Cells with Biparental-Like Expression of Imprinted Genes Generate Cortical-Like Neurons That Integrate into the Injured Adult Cerebral Cortex

Abstract: One strategy for stem cell-based therapy of the cerebral cortex involves the generation and transplantation of functional, histocompatible cortical-like neurons from embryonic stem cells (ESCs). Diploid parthenogenetic Pg-ESCs have recently emerged as a promising source of histocompatible ESC derivatives for organ regeneration but their utility for cerebral cortex therapy is unknown. A major concern with Pg-ESCs is genomic imprinting. In contrast with biparental Bp-ESCs derived from fertilized oocytes, Pg-ESCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
(132 reference statements)
1
6
0
Order By: Relevance
“…Similar to paAFSCs, paASCs were found to possess the expression of major pluripotency genes such as Oct4 and Nanog, but Sox2 had an apparently reduced expression in both cell lines. However, paASCs were found to have the capability to form teratomas and also contributed to E10.5 chimaeras, which confirmed their developmental pluripotency in vivo, consistent with previous studies [7,11,26,27]. Haploid embryonic stem cells from monogenetic gametes have been established as having a high expression of pluripotent genes and contributing to chimaera, though flow sorting every few passages for haploid cells is inevitable [28,29].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to paAFSCs, paASCs were found to possess the expression of major pluripotency genes such as Oct4 and Nanog, but Sox2 had an apparently reduced expression in both cell lines. However, paASCs were found to have the capability to form teratomas and also contributed to E10.5 chimaeras, which confirmed their developmental pluripotency in vivo, consistent with previous studies [7,11,26,27]. Haploid embryonic stem cells from monogenetic gametes have been established as having a high expression of pluripotent genes and contributing to chimaera, though flow sorting every few passages for haploid cells is inevitable [28,29].…”
Section: Discussionsupporting
confidence: 88%
“…However, whether the low expression of Sox2 triggered the increased expression of Cdx2 and whether this gene expression pattern is related to imprinting genes in paAFSCs and paASCs require further exploration. Moreover, the expression of Sox2 in haploid stem cells is same as that in normal mouse ESCs [5,28,29,31], but no study of parthenogenetic diploid stem cells has shown the expression status of Sox2 [7,26,27]. Thus, whether the low expression of Sox2 is a common property of parthenogenetic diploid stem cells also needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E14Tg2a mouse ESCs and their CRISPRa and CRISPRi derivatives were cultivated on gelatine coated dishes and maintained pluripotent in Serum/Lif media as described (Varrault et al 2018). Organoids were generated in 96-well (U-bottom) Ultra-Low Attachment plates (Sumitomo) by seeding 3000 ESCs in corticogenesis medium 1: DMEM/F-12/GlutaMAX supplemented with 10% KSR, 0.1 mM of non-essential amino acids, 1 mM of sodium pyruvate, 50U/ml penicillin/streptomycin, 0.1 mM of 2-mercaptoethanol (Sigma), 1 µM DMH1-HCl (in house synthesized, Vanderbilt University) and 240 nM IWP-2 (Tocris).…”
Section: Methodsmentioning
confidence: 99%
“…This is a key step for activation of reconstructed oocytes/embryos in the animal cloning program (Kishigami et al, 2006). Previously it was demonstrated that embryonic stem cell have been derived from the parthenotes (Varrault et al, 2018). These embryonic stem cells are equally competent to fertilized embryonic stem cell in terms of pluripotency and proliferation (Ju et al, 2008).…”
Section: Introductionmentioning
confidence: 99%